1993
DOI: 10.1093/brain/116.4.781
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of histological diagnosis including grading in gliomas biopsied by image-guided stereotactic technique

Abstract: We report clinical and pathological data of 419 image-guided stereotactic biopsies. In the present series the diagnostic yield, estimated by comparing the original histological diagnoses with follow-up data, was found to be approximately 94% in gliomas. As it has been suggested that malignancy of astrocytic gliomas may be considerably underestimated in the small tissue samples obtained by stereotactic biopsy, we have reviewed 160 adult, diffuse supratentorial astrocytic tumours, correlating the original Kernoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 0 publications
2
30
0
6
Order By: Relevance
“…Several studies have compared the immediate biopsy diagnosis, based on frozen sections or smears, with that of the permanent biopsy sections and have reported high accuracy (Apuzzo et al, 1987;Broggi et al, 1984;Gaudin et al, 1997;Kleihues et al, 1984;Ostertag et al, 1980;Revesz et al, 1993;Willems and Alva-Willems, 1984) or have concluded that the accuracy was high, based on survival studies (Gaudin et al, 1997;Revesz et al, 1993). However, only a few studies, using small sample sizes, have addressed the accuracy of diagnoses based on the biopsy specimen relative to those based on the resected surgical specimen (Broggi et al, 1984;Chandrasoma et al, 1989;Feiden et al, 1991;Kleihues et al, 1984;Scerrati and Rossi, 1984) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the immediate biopsy diagnosis, based on frozen sections or smears, with that of the permanent biopsy sections and have reported high accuracy (Apuzzo et al, 1987;Broggi et al, 1984;Gaudin et al, 1997;Kleihues et al, 1984;Ostertag et al, 1980;Revesz et al, 1993;Willems and Alva-Willems, 1984) or have concluded that the accuracy was high, based on survival studies (Gaudin et al, 1997;Revesz et al, 1993). However, only a few studies, using small sample sizes, have addressed the accuracy of diagnoses based on the biopsy specimen relative to those based on the resected surgical specimen (Broggi et al, 1984;Chandrasoma et al, 1989;Feiden et al, 1991;Kleihues et al, 1984;Scerrati and Rossi, 1984) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…It is less invasive, safe and carries less risk of complication. Revesz et al [2] reported the data of 419 patients undergoing stereotactic biopsy, where the diagnostic rate of glioma reached 94%. Giunta et al [3] reported a series of 35 patients with brain stem tumors in whom the diagnosis was confirmed in 29 by stereotactic biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic biopsy has a reported diagnostic accuracy of 89-97% and is a reliable tool for obtaining a diagnosis in intra-axial brain lesions in adults [6][7][8][9][10][11] and children [12]. Despite the high reliability of CT scan based stereotactic biopsies, efforts are made to increase the diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%